2020
DOI: 10.1111/jzs.12356
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses on Western PalearcticLasiommatareveal a mosaic of nascent butterfly species

Abstract: Satyrinae butterflies occurring in the Mediterranean apparently have reduced gene flow over sea straits, and for several species, recent wide‐scale biodiversity surveys indicate the existence of divergent mitochondrial lineages. Here, we apply an integrative approach and examine the phylogeography of the genus Lasiommata in the Western Palearctic. Our research comprised molecular analyses (mitochondrial and nuclear DNA) and geometric morphometrics (wings and genitalia) for two main species groups, and a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Thus, PROTAX can deal with any (small or large) interspecific genetic distance above zero, whereas some procedures defining de novo groups based exclusively on single-marker genetic distances or phylogenetic tree (like the BIN approach) can produce cases of over-splitting or lumping because coalescence times can largely vary among taxa (e.g. 20 for tribes of Nymphalidae). Because PROTAX also takes into account haplotype frequency, lack of monophyly due to low-frequency haplotypes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PROTAX can deal with any (small or large) interspecific genetic distance above zero, whereas some procedures defining de novo groups based exclusively on single-marker genetic distances or phylogenetic tree (like the BIN approach) can produce cases of over-splitting or lumping because coalescence times can largely vary among taxa (e.g. 20 for tribes of Nymphalidae). Because PROTAX also takes into account haplotype frequency, lack of monophyly due to low-frequency haplotypes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Spialia sertorius-rosae 17 , Iphiclides podalirius-feisthamelii 18 , Melitaea phoebe-ornata 19 ), paraphyly (e.g. Lasiommata spp 20 .) and reproductive compatibility among deeply divergent lineages (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic ranges were quantified as follows: we obtained occurrence data over Europe for all focal species with a resolution of 60’ latitude and 30’ longitude by critically revising the data from the Distribution Atlas of European Butterflies and Skippers (Kudrna et al , 2011) and by adding data from Roger Vila’s collection stored at Institut de Biologia Evolutiva (Barcelona). To calculate range overlap we applied the biodecrypt function (Platania et al , 2020) of the recluster R package (Dapporto et al , 2013). This function computes alpha hull with a given concavity ( α ) and evaluates the area of overlap among pairs of species.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the taxonomy of all 496 European species (Wiemers et al , 2018) is well resolved and a complete, multilocus phylogeny of all European taxa exists (Dapporto et al , 2019). This combined with extensive DNA barcode reference libraries (Dapporto et al , 2019, Dincă et al , 2015), facilitates the identification of species (especially in the case of cryptic taxa) and provides extensive sampling of sister species pairs, many of which abut at narrow contact zones (Dennis et al , 1991, Platania et al , 2020, Vodă et al , 2015) (Figure 1). Secondary contact zones have been described in detail for several European taxa, including Spialia orbifer and S. sertorius (Lorkovic, 1973), the Italian Pontia hybrid zone (Porter et al , 1997) and the contacts between Iphiclides podalirus and I. feisthamelii and between Melanargia galathea and M. lachesis along the Pyrenees (Gaunet et al , 2019b, Habel et al , 2017, Wohlfahrt, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases it has been shown that it is very difficult to assign a particular specimen to a particular species. Until now there are no unequivocal and universal criteria for species delimitations when the underlying evolutionary processes and phylogenies are taken into consideration (e.g., Zachos et al, 2013;González et al, 2018;Stanton et al, 2019;Platania et al, 2020), and even for the existence of species at all (Ereshefsky, 1998;Willis, 2017;Reydon & Kunz, 2019). At the conceptual level, more than 26 different species concepts have been suggested (Zachos, 2016) but at a practical level even the most widely acclaimed criterion of reproductive isolation (Mayr, 1969(Mayr, , 1982 is not robust as has been shown on numerous occasions (e.g., McDonald and Koehn, 1988;Mallet, 2005;Kijewski et al, 2006;Harrison & Larson, 2014;Jančúchová-Lásková et al, 2015;Crossman et al, 2016;Fraïsse et al, 2016;Potkamp & Fransen, 2019).…”
Section: Introductionmentioning
confidence: 99%